Morfologi dan Sintaksis: Hubungan Pembentukan Kata dengan Struktur Kalimat - Situmeang, Marisa Septiana; Sihombing, Melica; Sidabutar, Putri Angelina; Marlina, Theresia; Gultom, Yopita; Putri, Herlina Jasa (CV. Eduartpia Publisher, 2025)
The relationship between morphology and syntax is a fundamental aspect of linguistic analysis. Morphology plays a role in word formation through processes such as affixation, reduplication, and composition, while syntax organizes the arrangement of these words into meaningful sentence structures. This research aims to examine the relationship between these two aspects in Indonesian by using a qualitative descriptive approach. The data used in the study were obtained from various written sources, including grammar books, journals of scientific articles of literary works. The results show that morphological changes in a word can affect its syntactic function, for example through the derivation process which allows a verb to function as a noun in a sentence. In addition, it was found that the understanding of morphosyntax is still limited, even among linguistics students. Therefore, more interactive and example-based learning methods are needed to improve the understanding of this concept. The findings from this study have implications in the areas of language education, translation, and natural language processing. A better understanding of the relationship between morphology and syntax allows for more in-depth linguistic analysis, thereby improving communication effectiveness in various academic and practical contexts